PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN DAN LEMBAR KERJA SISWA MODEL PEMBELAJARAN CORE DENGAN TEKNIK MIND MAPPING POKOK BAHASAN BANGUN RUANG SISI LENGKUNG KELAS IX SMP - Khoiriyah, Jannatul; Suharto, S; Trapsilasiwi, Dinawati (Kadikma, 2014)
Abstract. The research aims is to know the process and the result of development lesson plan and student worksheets based on CORE (connecting organizing reflecting extending) learning model with technique of mind mapping for curved space topic at ninth grade of junior high school. Learning instruments development model refers to 4D Thiagarajan models which has 4 steps namely define, design, develop, and disseminate. This research has two products namely lesson plan and student worksheets. Based on validation process and tryout, the result shows that the coefficient of validity reachs 0,60, the percentages of teacher’s activities and students’ responses are above 80%, and the percentage of students’ activitie is above 10% - 20%, it can be concluded that the lesson plan and student worksheet had fullfiled the validity, practice, and effective criteria. Keywords : 4D Thiagarajan models, CORE learning model, technique of mind mapping, curved space.